Narrativa e Resistência em Selva Trágica, de Hernâni Donato - Sirino, Tallyssa Izabella Machado (2013)
This research aims to reflect about narrative and resistance as themes, represented on the novel Selva Trágica (2011),written by Hernâni Donato. The study of relations regarding space and literary representation of characters that, in the literary narrative of Selva Trágica, live under labor conflicts in a borderline space (Brazil-Paraguay) becomes the point from which and to which the reviews and interpretations of this study will converge. From the narrative s study, the inner structure is revealed as built by means of the representation of individuals explored by a Company, well-known as Companhia Mate Laranjeira, an argentine company of yerba mate processing, as external elements for the literary narrative. It is considered that the representation of herbals, on the narrative, in a borderline localization, in which characters live under constant shifts, regarding geographical, identity, cultural and linguistic changes, motivated by the labor fronts, becomes an structuring element of the narrative. Thus, the structural aspects such as the space and the characters are studied from the theoretical and methodological assumptions of the dialectic constitution of literature, based, particularly, on theoretical and analytical studies of Antonio Candido (2010), about the inherent relationship between internal and external elements in preparing aesthetics of the literary text. The studies on transiting identities, or in the context of boundary identities and alterity, are based on theoretical assumptions of Homi K. Bhabha (1998) and Stuart Hall (2009 and 2011). The saga of exploitation of yerba mate is understood as a metaphor for the strength of the ruling power, because through such exploitation, the oppression is exerted on the man, subjugating the characters and enslaving them in the herbal space - degraded space - degrading, thereby, characters. Therefore in Selva Tragica, it is observed that resistance consists in bringing such degrading and oppressive situations afloat by the aesthetic-ideological choice inherent to the narrative construction of the author, and it is perceived that this strategy can be approximated to the reflections of novel construction by Adorno (2003), Benjamin (1987), Goldmann (1989) and Santiago (2002), as well as the notion of degraded hero of Lukacs (1965). Hence, this study enables the reflection on represented spatiality, as well as the relationships between space, theme, characters, identities, resistance and territoriality in the literary work Selva Tragica as representative of a borderline literature corpus